Access and opportunities for Peruvian women in STEM fields in the Latin American context: A systematic review - Cruz, Maria Angela Salinas; Somoza, Alicia Roxana Chávez; Salés, Eduardo Paul Vilchez; Swayne, Dora Viviana Rosa Vega (Edelweiss Applied Science and Technology, 2025)
This article aimed to describe the authors’ main results on the access and opportunities that Peruvian women have in STEM careers in the Latin American context. A systematic review of the literature was developed, complying with the PRISMA Protocol. In addition, the sources in the Scopus and Web of Science databases were filtered and reviewed using Boolean operators and combined descriptors until 24 articles that met the search criteria were found. Fundamental aspects such as Peruvian women scientists, access to scientific careers, their opportunities, and their scientific and academic productivity are presented. The results of the review demonstrated that the situation of university access for Peruvian women compared to women from other Latin American countries has improved in recent years; however, they occupy the last place in the gender opportunity gap, and less than half of women with STEM careers are dedicated to research, minimizing their role within the scientific field. Therefore, it is relevant to conduct research that allows obtaining relevant and in-depth information about the participation of Peruvian and Latin American women scientists and the impact on future generations.